COMPARATIVE ANALYSIS OF QUALITATIVE AND QUANTITATIVE PARAMETERS OF TRANSIENT MYOCARDIAL ISCHEMIA AND 24-HOUR pH MONITORING IN PATIENTS WITH CORONARY HEART DISEASE AND GASTROOESOPHAGEAL REFLUX DISEASE - O. S. Fedoseeva; Yu. N. Fedulaev; I. M. Korochkin; L. V. Kuzmenkova (Российский кардиологический журнал, 2011)
In 122 patients with chest pain syndrome, anamnestic and clinical data, as well as the results of oesophagogastroduodenoscopy, veloergometry, 24-hour ECG monitoring, and 24-hour pH monitoring, were analysed. All participants were divided into three groups: Group 1 – patients with gastro-oesophageal reflux disease (GERD) only; Group 2 – patients with coronary heart disease (CHD) only; and Group 3 – patients with GERD and CHD. Adverse mutual effects of GERD and CHD were demonstrated, based on clinical and instrumental data. Primary and secondary ECG changes were identified, and a method for simultaneous 24-hour ECG and pH monitoring was proposed as a differential diagnostic tool in patients with chest pain syndrome.